2010
DOI: 10.1371/journal.pone.0013953
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Footprint of Diabetes: A Multiplatform Metabolomics Study in an Epidemiological Setting

Abstract: BackgroundMetabolomics is the rapidly evolving field of the comprehensive measurement of ideally all endogenous metabolites in a biological fluid. However, no single analytic technique covers the entire spectrum of the human metabolome. Here we present results from a multiplatform study, in which we investigate what kind of results can presently be obtained in the field of diabetes research when combining metabolomics data collected on a complementary set of analytical platforms in the framework of an epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
460
5
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(508 citation statements)
references
References 58 publications
38
460
5
5
Order By: Relevance
“…Increased plasma acylcarnitines and tryptophan and decreased plasma LPC(16:0), LPC(18:0), LPC(18:2) and phenylalanine were reported in treated T2DM patients [86]. Another study has shown changes in plasma amino acid and perturbation of metabolic pathways linked to 3-indoxyl sulfate, glycerophospholipids, free fatty acids and interaction with the bile acids in diabetic patients [87]. Fatty acids can improve insulin secretion in the basal or glucose stimulated states and fatty acids are essential for stimulus-secretion coupling in β-cells [88].…”
Section: Type 2 Diabetes (T2dm)mentioning
confidence: 97%
“…Increased plasma acylcarnitines and tryptophan and decreased plasma LPC(16:0), LPC(18:0), LPC(18:2) and phenylalanine were reported in treated T2DM patients [86]. Another study has shown changes in plasma amino acid and perturbation of metabolic pathways linked to 3-indoxyl sulfate, glycerophospholipids, free fatty acids and interaction with the bile acids in diabetic patients [87]. Fatty acids can improve insulin secretion in the basal or glucose stimulated states and fatty acids are essential for stimulus-secretion coupling in β-cells [88].…”
Section: Type 2 Diabetes (T2dm)mentioning
confidence: 97%
“…These findings from human patients can be summarised as follows: i) As expected, diabetic patients exhibited differences in glucose metabolism. Patients with T1DM under insulin deprivation (Lanza et al 2010) or in T2DM (Li et al 2009, Suhre et al 2010) demonstrated elevated glucose or mannose levels compared with healthy controls. Furthermore, in both T1DM and T2DM patients (Messana et al 1998, Zuppi et al 2002 increased lactate levels were observed, at which these levels increased with the grade of glucosuria in T2DM patients (Messana et al 1998).…”
Section: Patient Investigationsmentioning
confidence: 99%
“…Cross-sectional approaches have identified 'metabolic signatures' associated with insulin resistance and type 2 diabetes [82,83], and thus indicated their potential as prognostic biomarkers for type 2 diabetes risk.…”
Section: Lipids and Small Metabolitesmentioning
confidence: 99%